Perspektif Dan Peran Sosiologi Ekonomi Dalam Pembangunan Ekonomi Masyarakat Berdasarkan Al-Qur’an - Wulandari, Desi; Nur, Saprida; Sukma, Mhd. Bintang; Hardiansyah, Riki; Siregar, Rini Wahyuni (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2023)
Conventional economic sociology discourse has not succeeded in realizing its ideals social welfare. It is proven that there are still many social inequalities and poverty in various parts of the world. This situation results in sociological conflict economy that takes many victims. World peace and progress of civilization is still difficult to realize because it is burdened with the responsibility of resolving conflicts. A comprehensive solution is needed, solving the root of the problem as well treat all the impacts it causes. Based on these facts then, The problem with this research is that there is no economic sociology model comprehensive approach that is able to overcome the problem of social inequality and Poverty as a source of conflict. Therefore, this research aims to find an economic sociology model that could be a practical solution for all aspects of current and future economic sociology problems. The method used in this research is a qualitative, research-based method literature, verses of the Koran, research publications, journals, seminars and articles. The interpretation method used is the thematic interpretation method (tafsir maudhû'i) because it is seen as being able to produce comprehensive, systematic and interpretations easy to understand. This research found that the economic sociology model in The Al-Qur'an perspective focuses on fulfilling 5 principles as guidelines The main thing for all understanding of economic sociology, namely the divine principle-principlewelfare, the principle of justice, the principle of distribution of wealth, and the principle of anticipation crisis